Allergen-specific immunotherapy of Hymenoptera venom allergy – also a matter of diagnosis - Maximilian Schiener; Anke Graessel; Markus Ollert; Carsten B. Schmidt-Weber; Simon Blank (Human Vaccines & Immunotherapeutics, 2017)
Stings of hymenoptera can induce IgE-mediated hypersensitivity reactions in venom-allergic patients, ranging from local up to severe systemic reactions and even fatal anaphylaxis. Allergic patients' quality of life can be mainly improved by altering their immune response to tolerate the venoms by injecting increasing venom doses over years. This venom-specific immunotherapy is highly effective and well tolerated. However, component-resolved information about the venoms has increased in the last years. This knowledge is not only able to improve diagnostics as basis for an accurate therapy, but was additionally used to create tools which enable the analysis of therapeutic venom extracts on a molecular level. Therefore, during the last decade the detailed knowledge of the allergen composition of hymenoptera venoms has substantially improved diagnosis and therapy of venom allergy. This review focuses on state of the art diagnostic and therapeutic options as well as on novel directions trying to improve therapy.